A comprehensive environmental assessment of beef production and consumption in the United States. (20th May 2023) - Putman, Ben; Rotz, C. Alan; Thoma, Greg
Abstract: Life cycle assessments of have been completed documenting the environmental sustainability of beef, but these studies have often focused on specific cattle production systems with an emphasis on global warming potential. A need exists for a national-scale full life cycle assessment of beef production through consumption in the United States. Process level simulation of archetypical cattle production systems throughout the nation were combined with information gathered for harvest, processing, retail, and consumption of beef to provide inventory data for a cradle-to-grave life cycle assessment. A set of 18 environmental impact categories were quantified, and important sources of each were identified. In 13 of the categories, the major sources of impact were related to cattle production, and for 10 of these categories, cattle production and related upstream sources contributed more than half of the total impact. These categories were fine particulate matter, global warming, land use, mineral resource scarcity, ozone formation, stratospheric ozone depletion, terrestrial acidification, and water consumption. Categories where most of the impact occurred post farmgate were fossil resource scarcity, freshwater ecotoxicity, freshwater eutrophication, human carcinogenic toxicity, human non-carcinogenic toxicity, ionizing radiation, marine ecotoxicity, and terrestrial ecotoxicity. Mitigation strategies for reducing these environmental impacts are normally specific to the impact category. Because electricity use is an important contributor to many of the potential impacts throughout the full chain, reducing electricity use is an important mitigation strategy. We evaluated the sensitivity associated with greening of the electric grid in which the Northeast US power grid, which has a larger percentage of renewables, was used as the source of electricity for all systems. The impact remained constant or were reduced in 15 of the 18 impact categories including a 6% reduction in global warming and 22% reduction in particulate matter formation. Another major contributor to all impact categories was food loss and waste. A 50% reduction in food waste, primarily by the consumer, resulted in an across-the-board reduction of approximately 11% in each of the impact categories, which makes food waste reduction one of the most important strategies for improving the environmental sustainability of beef. This assessment provides a current baseline for evaluating mitigation strategies and measuring future improvements in sustainability for the U.S. beef industry. Highlights: a national baseline environmental profile for US beef production and consumption. AsSessed full supply chain including quick- and full-serve restaurants and home use. 160 archetypical cattle production systems across all 50 states were simulated. 50% reduction in consumption food loss resulted in ∼11% in each impact category. Average cradle-to-grave carbon footprint of beef produced and consumed is 42.7 kg CO2e /kg.